Do fine motor skills contribute to early reading development?. (17th August 2016) - Suggate, Sebastian; Pufke, Eva; Stoeger, Heidrun
Abstract : Background: Little is known about how fine motor skills (FMS) relate to early literacy skills, especially over and above cognitive variables. Moreover, a lack of distinction between FMS, grapho‐motor and writing skills may have hampered previous work. Method: In Germany, kindergartners ( n = 144, aged 6;1) were recruited before beginning formal reading instruction and were administered a host of FMS, early reading skills and cognitive measures. Results: Analyses indicate that FMS related less strongly than grapho‐motor skills to emergent literacy skills. Controlling for grapho‐motor and cognitive skills, FMS did not generally explain unique variance in emergent literacy skills. Conclusions: The link between reading and motor skills is highly differential. Findings did not suggest that pure FMS played a significant role in early reading development, however, its close cousin grapho‐motor skills – even when devoid of the cognitive knowledge of letters – did. Implications for practice: What is already known about this topic: Fine motor skills (FMS) are considered an important school readiness indicator FMS play a role in cognition and language development Some research suggests that FMS might be important for reading What this paper adds: First study to look differentially at FMS and emergent literacy FMS was considered separately from grapho‐motor and handwriting skill Links between these motor skills and a broad range of emergent literacy and cognitive skills were investigated Implications for practice and/or policy: FMS may be important in the development of grapho‐motor skills Grapho‐motor skills appear, in turn, linked to reading Fostering children's grapho‐motor skills may be important in kindergarten